(untitled) (Quinto Sol, 2021)
This article analyzes the processes of agrarian change associated to the first expansion of the extensive dryland agriculture frontier in middle-western Dry Chaco (northwestern Argentina) during the 1960-1990 period. The singularity of the case in relation to other agrarian spaces of the region is that soybean cultivation was introduced in the 1960s in the farming colonies of that area, constituting one of the first spaces in Argentina where soybean was produced commercially. This experience constituted the precedent in relation to which public organizations and private companies produced knowledge and technology to achieve economically positive results on what until then was a marginal space, based on a crop with no national background in semi-arid spaces. In the 1970s, investors from other sectors of the economy acquired land and imprinted a business model for agriculture in the study area. However, during the 1980s soil degradation became a general problem that slowed the expansion of the previous decade.